2014
DOI: 10.1097/pas.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell Lymphomas With Cytotoxic Phenotype in Patients With Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma

Abstract: Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL) is relatively common, and patients occasionally develop other neoplasms; however, patients who develop other types of lymphomas are rare. We encountered 3 patients with CLL/SLL (one 59-y-old man and 2 women aged 56 and 66 y) who developed T-cell lymphomas. Both women developed ALK anaplastic large cell lymphomas (ALCLs), whereas the man developed CD8 peripheral T-cell lymphoma, not otherwise specified. All 3 T-cell lymphomas expressed granzyme B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…This is in agreement with authors who observed a development of peripheral T-cell lymphomas with cytotoxic phenotype in the patients with B-CLL [9,10].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with authors who observed a development of peripheral T-cell lymphomas with cytotoxic phenotype in the patients with B-CLL [9,10].…”
Section: Discussionsupporting
confidence: 82%
“…Large granular lymphocytic leukemia is the doi: 10.7243/2052-7896-3-4 clonal expansion of either CD8 positive cytotoxic T-cells (80%) or natural killer cells (20%). Normal number of LGL (morphology is depicted in Figure 1) in the peripheral blood is 100 to 300 LGL/microliter (µL) (0.1-0.3X10 9 LGL/L) or 5% to 15% of peripheral blood lymphocytes. According to the immunophenotype, LGL are divided in two types of cells: CD8 and CD3 positive suppressor/cytotoxic T-cells and natural killer cells (CD3 negative, CD16 positive LGL).…”
Section: Introductionmentioning
confidence: 99%
“…2 In the present patient, R-CHOP continued to be effective against advanced B-CLL, whereas the anti-CD30 antibody exhibited transient effects on PTCL. Previous studies demonstrated the efficacy of autologous or allogeneic hematopoietic stem cell transplantation (HSCT) for composite lymphoma during remission.…”
Section: Discussionmentioning
confidence: 85%
“…Among these T-cell lymphomas, 9 cases of PTCL-NOS have been reported, followed by 4 cases of ALCL. 2 These reports documented that the time from the onset of B-CLL to lymphoma development was 0.8 to 14 years, with a survival time of 2 days to 2 years after the diagnosis of composite lymphoma. Thus, composite lymphoma occurs even in the early stage of B-CLL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation